Mechanisms for variable expressivity of inherited SCN1A mutations causing Dravet syndrome. Issue 6 (3rd June 2010) - Depienne, Christel; Trouillard, Oriane; Gourfinkel-An, Isabelle; Saint-Martin, Cécile; Bouteiller, Delphine; Graber, Denis; Barthez-Carpentier, Marie-Anne; Gautier, Agnès; Villeneuve, Nathalie; Dravet, Charlotte; Livet, Marie-Odile; Rivier-Ringenbach, Clothilde; et al.
Abstract : Background: Mutations in SCN1A can cause genetic epilepsy with febrile seizures plus (GEFS+, inherited missense mutations) or Dravet syndrome (DS, de novo mutations of all types). Although the mutational spectra are distinct, these disorders share major features and 10% of DS patients have an inherited SCN1A mutation. Objectives and patients: 19 selected families with at least one DS patient were studied to describe the mechanisms accounting for inherited SCN1A mutations in DS. The mutation identified in the DS probands was searched in available parents and relatives and quantified in the blood cells of the transmitting parent using quantitative allele specific assays. Results: Mosaicism in the blood cells of the transmitting parent was demonstrated in 12 cases and suspected in another case. The proportion of mutated allele in the blood varied from 0.04–85%. In the six remaining families, six novel missense mutations were associated with autosomal dominant variable GEFS+ phenotypes including DS as the more severe clinical picture. Conclusion: The results indicate that mosaicism is found in at least 7% of families with DS. In the remaining cases (6/19, 32%), the patients were part of multiplex GEFS+ families and seemed to represent the extreme end of the GEFS+ clinical spectrum. In this latter case, additional genetic or environmental factors likely modulate the severity of the expression of the mutation.